Cilostazol suppresses β‐amyloid production by activating a disintegrin and metalloproteinase 10 via the upregulation of SIRT1‐coupled retinoic acid receptor‐β. Issue 11 (5th June 2014) - Lee, Hye Rin; Shin, Hwa Kyoung; Park, So Youn; Kim, Hye Young; Lee, Won Suk; Rhim, Byung Yong; Hong, Ki Whan; Kim, Chi Dae
<x xml:space="preserve">Abstract</x> The accumulation of plaques of β‐amyloid (Aβ) peptides, a hallmark of Alzheimer's disease, results from the sequential cleavage of amyloid precursor protein (APP) by activation of β‐ and γ‐secretases. However, the production of Aβ can be avoided by alternate cleavage of APP by α‐and γ‐secretases. We hypothesized that cilostazol attenuates Aβ production by increasing a disintegrin and metalloproteinase 10 (ADAM10)/α‐secretase activity via SIRT1‐coupled retinoic acid receptor‐β (RARβ) activation in N2a cells expressing human APP Swedish mutation (N2aSwe). To evoke endogenous Aβ overproduction, the culture medium was switched from medium containing 10% fetal bovine serum (FBS) to medium containing 1% FBS, and cells were cultured for 3∼24 hr. After depletion of FBS in media, N2aSwe cells showed increased accumulations of full‐length APP (FL‐APP) and Aβ in a time‐dependent manner (3–24 hr) in association with decreased ADAM10 protein expression. When pretreated with cilostazol (10–30 μM), FL‐APP and Aβ levels were significantly reduced, and ADAM10 and α‐secretase activities were restored. Furthermore, the effect of cilostazol on ADAM10 expression was antagonized by pretreating Rp‐cAMPS and sirtinol and by SIRT1‐gene silencing. In the N2aSwe cells overexpressing the SIRT1 gene, ADAM10, and sAPPα levels were significantly elevated. In addition, like all‐trans retinoic acid, cilostazol enhanced the protein expressions of RARβ and ADAM10, and the cilostazol‐stimulated ADAM10 elevation was significantly attenuated by LE135 (a RARβ inhibitor), sirtinol, and RARβ‐gene silencing. In conclusion, cilostazol suppresses the accumulations of FL‐APP and Aβ by activating ADAM10 via the upregulation of SIRT1‐coupled RARβ. © 2014 Wiley Periodicals, Inc.